2022
DOI: 10.1021/acs.biomac.2c01045
|View full text |Cite
|
Sign up to set email alerts
|

Direct and Indirect Cationization of Cellulose Nanocrystals: Structure–Properties Relationship and Virus Capture Activity

Abstract: Due to increasing public concern over hygiene, there have been many studies investigating antimicrobial and antiviral agents recently. With the aim of developing biobased virucidal/virus capture agents, we report a chemical modification of the cellulose nanocrystals (CNCs) surface with poly(2-dimethylamino) ethyl acrylate) methyl chloride quaternary salt (Q-PDMAEA) to introduce the positively charged functional groups. The surface of CNCs was modified through direct and indirect graft polymerization. Subsequen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 45 publications
0
2
0
Order By: Relevance
“…Previously, we have also demonstrated that the presence of specific functional groups on the nanocellulose imparts antiviral properties. 5,6 Recently, chitosan has been widely used in medicine. 7,8 This linear polysaccharide, consisting of randomly distributed β-(1 → 4)-linked Dglucosamine (GlcN) and N-acetyl-D-glucosamine (GlcNAc) units, is commonly used in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Previously, we have also demonstrated that the presence of specific functional groups on the nanocellulose imparts antiviral properties. 5,6 Recently, chitosan has been widely used in medicine. 7,8 This linear polysaccharide, consisting of randomly distributed β-(1 → 4)-linked Dglucosamine (GlcN) and N-acetyl-D-glucosamine (GlcNAc) units, is commonly used in biomedical applications.…”
Section: Introductionmentioning
confidence: 99%
“…This surface charge has been used to remove viruses in water treatment using coagulation agents and polyelectrolytes. Previously, we have also demonstrated that the presence of specific functional groups on the nanocellulose imparts antiviral properties. , Recently, chitosan has been widely used in medicine. , This linear polysaccharide, consisting of randomly distributed β-(1 → 4)-linked D-glucosamine (GlcN) and N -acetyl-D-glucosamine (GlcNAc) units, is commonly used in biomedical applications. However, the applications of unmodified chitosan are limited due to its poor water solubility and pH-dependent charge behavior .…”
Section: Introductionmentioning
confidence: 99%